Hydroxycinnamic acid amides in rice: biosynthesis, distribution, function, and implication for crop development - Xue, Rongrong; Gao, Ning; Chen, Jing; Wu, Zicha; Sun, Na; Li, Ying; Gong, Miuhua; Zeng, Rensen; Song, Yuanyuan; Chen, Dongmei; Wang, Jie (Frontiers in Plant Science, 2025)
Rice (Oryza sativa L.) is critical for providing energy and nutrients and ensuring food security for over half of the world’s population. However, like other crop plants, rice is vulnerable to various environmental stresses. To combat these stresses, plants accumulate numerous secondary metabolites known as phytoalexins. Hydroxycinnamic acid amides (HCAAs) are a widely distributed class of phenylpropanoid-derived phytoalexins with diverse biological functions. Increasing evidence highlights their pivotal roles in both abiotic and biotic stress responses, as well as in the modulation of plant growth and development. HCAAs are synthesized by inducible hydroxycinnamoyl transferases acting on the free amines and hydroxycinnamic acids, which provide HCAAs with a variety of metabolic, chemical, and functional capabilities due to diverse combinations among the parent compounds. This review synthesizes current knowledge to emphasize the importance of rice HCAAs, providing a comprehensive examination of their biosynthesis, distribution, biological functions, and regulatory mechanisms, particularly in relation to stress tolerance. Furthermore, the review seeks to further explore beneficial properties of HCAAs, as well as to advance their potential application in genetic breeding to develop elite crops.